A Proposed Object Schema Management Tool - Lim, Tong Ming; Lee, Sai Peck (Malaysian Journal of Computer Science, 2002)
Object Schema Management Tool (OSMT) is the primary graphical component in the Object Schema Management Facility (OSMF) that provides services such as remove a class, add a class, delete a class and manage a class for a business class domain [5]. In addition, the Object Schema Management Facility (OSMF) also contains a set of language constructs for Object Schema Language (OSL), which manages Business Class Schemas (BCS) for business domains in a persistence framework [1, 2, 3, 4]. This paper discusses the enhancements and functionalities completed for the latest version of OSMT. A discussion on various approaches that a class schema is managed and maintained in DBMSs currently is presented in the subsequent section. It gives an overview of a GUI-based business class schema tool, the generation of business classes in a separate text file manually through the Interface Definition Language (IDL) and the creation of business class schemas using OSL as proposed in this research. Next, the OSMF component is examined in greater detail. The paper also examines pros and cons of the OSMT component and discusses possible OSMT enhancements for the current OSMF component in the framework.